A critical review of international print advertisements: evolutionary analysis, assessment and elucidations, from 1965 to 2020. Issue 5 (30th June 2021) - Vadalkar, Suniti; Chavan, Gitesh; Chaudhuri, Ranjan; Vrontis, Demetris
Abstract : Purpose: Amidst the plethora of mass communication methods that technology bestowed business with, print advertisements still remain an effective and widely utilized advertising tool, and retain a diachronically venerable position in international marketing practice. Bar and transcending mere academic fascination or curiosity, this research provides insights into the past, an understanding of the present and an outlook into the future. In this vein, through a methodical and comprehensive critical review of extant literature on print advertisements since 1965, this research aims to identify gaps in extant knowledge, to map its trends and divergences, to trace its paradigm shifts and to ultimately develop agendas for truly significant future research. Design/methodology/approach: This spatial-temporal study reviews 256 methodically selected articles, using VantagePoint software, and adopts a novel methodology through natural language processing (NLP), text mining, auto-correlation maps, and bubble maps to conduct and present a robust analysis and explicit findings. Findings: Using also the VOSviewer for density and network visualization, the results identify the predominant literature themes and, conversely, the relatively under-researched areas, and provide a more insightful collective interpretation of extant works, while laying the foundation for future research of greater value and significance to academia and industry. Originality/value: This study transcends the partial and/or limited analyses and perspectives of extant literature to present scholars with the first comprehensive and long term meta-analysis or systematic study of print advertising, with explicit findings of both scholarly and executive worth.